2006
DOI: 10.1002/ange.200503042
|View full text |Cite
|
Sign up to set email alerts
|

Chirally Aminated 2‐Naphthols—Organocatalytic Synthesis of Non‐Biaryl Atropisomers by Asymmetric Friedel–Crafts Amination

Abstract: Chinaalkaloide werden für die organokatalysierte asymmetrische Friedel‐Crafts‐Aminierung von 2‐Naphtholen genutzt. Diese Aminierungen verlaufen in hohen Ausbeuten mit bis 98 % ee und haben zu einer neuen Klasse von Nicht‐Biaryl‐Atropisomeren geführt. Die Rotationsbarrieren der chiralen aminierten 2‐Naphthole wurden experimentell und mithilfe von Rechnungen untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…A great disadvantage, however, aside from the issue of CÀH regioselectivity, resides in the necessity for pre-activation or pre-oxidation of the coupling partner such that it becomes sufficiently reactive for the condensation reaction to occur. To our knowledge, no dehydrogenative aromatic amination reaction has ever been proposed, whether by electrophilic attack (Scheme 1) [4,5] or homolytic substitution (HAS), [3] in which the oxidized aminating substrate would be generated in situ, thus avoiding pre-activation steps for both coupling partners, and moreover without metal [6] or halide additives. Such a reaction is desirable since it would be highly practical from a synthetic viewpoint and also sustainable, provided that O 2 can be utilized as sole terminal oxidant.…”
mentioning
confidence: 98%
“…A great disadvantage, however, aside from the issue of CÀH regioselectivity, resides in the necessity for pre-activation or pre-oxidation of the coupling partner such that it becomes sufficiently reactive for the condensation reaction to occur. To our knowledge, no dehydrogenative aromatic amination reaction has ever been proposed, whether by electrophilic attack (Scheme 1) [4,5] or homolytic substitution (HAS), [3] in which the oxidized aminating substrate would be generated in situ, thus avoiding pre-activation steps for both coupling partners, and moreover without metal [6] or halide additives. Such a reaction is desirable since it would be highly practical from a synthetic viewpoint and also sustainable, provided that O 2 can be utilized as sole terminal oxidant.…”
mentioning
confidence: 98%
“…[17][18][19] Although a variety of electron-rich aromatic compounds such as indoles, pyrroles, and furans have been successfully utilized as nucleophiles in 1,4-addition processes, [15,16] asymmetric reactions of phenol derivatives have been rarely studied. The difficulty in employing phenol derivatives in these processes could be a result of two intrinsic factors that are related to the fact that phenoxide anions generated in situ 1) often promote ligand exchange with metal catalysts, [17] and 2) can participate in reactions that take place with low levels of chemo-and regioselectivity.…”
mentioning
confidence: 99%
“…Unfortunately, the twostep reductive cleavage of the nitrogen-nitrogen bond to yield a carbamate-protected amine (without loss of optical purity) proceeded in somewhat disappointing yield. [36] Jørgensen et al also reported the first atroposelective organocatalytic Friedel-Crafts amination of 2-naphthols [39] (Scheme 9). Careful selection of the substituents on the aromatic ring permitted the identification of 8-amino-2-naphthols as precursors for configurationally stable aryl hydrazines.…”
Section: Electrophilic Aminationsmentioning
confidence: 95%